2019
DOI: 10.1177/0004867419876700
|View full text |Cite
|
Sign up to set email alerts
|

Clinical or gimmickal: The use and effectiveness of mobile mental health apps for treating anxiety and depression

Abstract: Objectives: The increase in ownership of smartphones and tablet devices has seen a worldwide government push, championed by the World Health Organization, towards digital healthcare services generally. Mental health has been a strong presence in the digitisation of healthcare because of the potential to solve some of the difficulties in accessing face-to-face services. This review summarises the recent history of e-mental health services and illuminates two very different paths. The first is the considerable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 78 publications
0
35
0
Order By: Relevance
“…Mental health services are changing. There are more than 10,000 mental health apps on the internet that are being used without much evidence of their effectiveness (Marshall et al 2020 ; Bergin and Davis 2020 ; Gould et al 2018 ). The explosion of mental health apps is the leading edge of future autonomous interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Mental health services are changing. There are more than 10,000 mental health apps on the internet that are being used without much evidence of their effectiveness (Marshall et al 2020 ; Bergin and Davis 2020 ; Gould et al 2018 ). The explosion of mental health apps is the leading edge of future autonomous interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed analysis of the research that accompanied 10 of the shortlisted apps is outside the scope of this paper, as this review is focused on the theoretical frameworks that underpin mental health apps. The quality and quantity of research into mental health apps has been detailed elsewhere [ 63 - 66 ]. However, the research found to accompany the apps listed here does appear to vary greatly in methodology; this reaffirms the claims of heterogeneity made in those literature reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the efficacy and effectiveness of mental health apps is limited (20,21). The research suffers from methodological deterrents (e.g., quality randomized controlled trials [RCTs] can be expensive and take years to run which is an impediment for the profit-driven app sector), heterogeneity across studies, no published replication studies to speak of, and a lack of independence (i.e., studies completed by researchers who have not had any association with the app) (22,23).…”
Section: The Evidence For Treating Symptoms Of Trauma With An Appmentioning
confidence: 99%